Justification of the choice of excipients during the development of the composition of “Pastinocard” tablets - N. А. Symonenko; O. S. Shpychak; O. S. Kukhtenko; Ye. A. Bezrukavyi; H. B. Yurieva (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2023)
The aim of the work is to justify the choice of excipients as components for the cardioprotective medicine “Pastinocard” tablets based on the domestic raw material of cultivated parsnip herb thick extract (CPHTE).